Procesos bioquímicos utilizados para la producción de bioetanol, biodiésel y biogás y su estado en Colombia (2017)
At present, there is a growing interest in mitigating the negative environmental impact generated by fossil fuels, so biofuels such as bioethanol, biodiésel and biogas have gained a significant role as alternatives from renewable energy sources with less impact on generation of atmospheric emissions, especially in transport uses. This is why the present article addresses key topics for the understanding and conceptualization of the biomass used, biochemical processes, tages of production, advantages and disadvantages of the biofuels mentioned. In the same way, it is made an approach to the progress of the implementation of these biofuels in Colombia and the researchs carried out for the production of bioethanol and biodiésel from raw materials that do not compromise the area of crops for food, as well as the challenges that the biogas to achieve its production on a large scale.